Tough cookie - Davidson, Diane Mott (Bantam Books, 2000)
Winter sports can be dangerous, but can they also be deadly? "Cooking at the Top!," Goldy's new TV show, is broadcast from one of Colorado's poshest ski areas. Unfortunately, she finds whipping up delicacies at 11,000 feet as perilous as skiing steep runs.